PENGEMBANGAN ALGORITMA PEMBANGKITAN G-CODE MESIN PERKAKAS CNC OKUMA&HOWA BERFASILITAS AUTOMATIC TOOL CHANGER DAN INDEXING PADA SOFTWARE CaSTPro - Martawirya, Y. Y; Arthaya, B; Sunil, A. W (Mesin, 2009)
This research deals with the integration product design phase, the process planning phase, and manufacturing operation planning phase through the feature-based product modeling. The competition in manufacturing industries demands a short production lead time. Autonomous Distributed Manufacturing Systems which has autonomic production elements enable to integrate those three phases through its autonomic product model. One of the proposed methodologies is a feature-based product modeling. At feature base product modeling, a product was defined as a model that is an interaction among features. Product model enable to identify the decreasing or additional volume influence to its geometry. At the final stage of product design, a model product enables to identify all features itâs has, features interaction, and features manufacturing sequences. At this research, G-Code was generated by product model that was designed by using CaSTPro software. The developed product model enriched its functionality with new facility that was a G-Code generation. As an example, G-Code fit for a horizontal machining center Okuma&Howa MILAC 4H FANUC 6M which was equipped with a tool changer and indexing had been developed.